A comprehensive study of the multiple effects of Y/Al substitution on O3-type NaNi0.33Mn0.33Fe0.33O2 with improved cycling stability and rate capability for Na-ion battery applications. Issue 32 (6th August 2020) - Li, Na; Wu, Kang; Lee, Yu Lin; Rongbin, Dang; Deng, Xin; Hu, Zhongbo; Xiao, Xiaoling
Abstract : The relationship between bond energy and electrochemical performance was studied through substituting Mn in O3-NaNi0.33 Mn0.33 Fe0.33 O2 oxide with Y and Al. Abstract : O3-NaNi0.33 Mn0.33 Fe0.33 O2 layered oxide has attracted increasing attention as one of the most promising materials for Na-ion battery applications due to air stability and environmental friendliness, but the complex phase transitions and inferior cycling stability are extremely challenging to overcome. Cation substitution has been widely used to stabilize crystal structures and improve electrochemical performance for SIBs. Based on past experimental results, it was discovered that the transition metal–oxygen bond energy of the introduced dopant is an important factor for optimizing electrochemical performance. In this study, we validated our hypothesis that yttrium (Y)-which possesses high bond energy for oxygen-is most likely to be an ideal doping element by conducting a comparative study of substituting Mn in O3-NaNi0.33 Mn0.33 Fe0.33 O2 layered oxide with aluminum (Al) and Y through elemental doping. As hypothesized, the electrochemical properties of NaNi0.33 Mn0.33 Fe0.33 O2 have increased markedly by introducing a small amount of Y and Al, and the Y-doped materials showed superior rate performance and cycling stability due to enhanced Na + diffusion reaction kinetics and layered structure stability. Furthermore, the substitution of Y for Mn can improve thermal stability and alleviate phase transformations. The improvement mechanism of Y substitution can be attributed to a larger d -spacing and stronger metal–oxygen bond. These results suggest that structural modulation is an effective strategy to reinforce electrochemical properties of layered oxides and provides some guidance about designing promising electrode materials.